Quality of life issue in psoriasis: A study from western Nepal - Kumar, A; Neupane, S; Shrestha, PR; Pun, J; Thapa, P; Manandhar, M (Nepal Journal of Medical Sciences, 2015)
Background: Psoriasis may have negative impact on a patient’s quality of life. Very few studies have examined this aspect in Nepalese population. Aim of this study was to evaluate the Quality of life (QOL) in chronic psoriatic patients by modified version of psoriasis disability index (PDI). Methods: Present cross sectional study was conducted in three major hospitals in western Nepal. One hundred chronic psoriatic patients of 18 years or more of age, with disease duration of six months or more and body surface area involvement of 10% or more were recruited. Clinical assessment was done with psoriasis area severity index (PASI) and quality of life was measured by modified version of PDI. Patients were managed as per indication. At the follow up at four weeks, improvement in PASI and improvement in QOL was measured. Statistical analysis by Chisquare test was done to assess the relation between severity of psoriasis and different items of quality of life. Results: Psoriasis has negative impact on all aspect of quality of life in Nepalese patients, as shown by score of modified version of PDI, which was 39.27% of total. There was significant improvement in PASI at follow up visit, from 23.29% to 15.35% of total. There was significant improvement in quality of life after treatment (modified version of PDI) from 39.27% to 32.66% of total. Conclusions: Psoriasis has negative impact on all aspect of quality of life in Nepalese patients. Nepal Journal of Medical Sciences Vol.3(2) 2014: 116-120